2019
DOI: 10.1002/cjce.23677
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of high‐temperature corrosion properties in simulated reducing‐sulphidizing atmospheres of the waterwall fireside in the boiler

Abstract: The presence of reducing atmospheres of the waterwall fireside in the boiler due to extensive use of low‐NOx combustion mode caused severe high‐temperature corrosion problems. In this study, high‐temperature sulphur corrosion properties of two types of low alloyed waterwall steel (15CrMoG and 12Cr1MoVG) in two kinds of reducing‐sulphidizing atmospheres were investigated by lab‐scale experiments. The experimental atmospheres and temperature were simulated according to field measurements in the boiler of a therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…Many studies [9][10][11][12][13][14][15] have been implemented to investigate the corrosion behaviors and mechanisms of boiler tubes. These studies are categorized into fireside corrosion and water/steamside corrosion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies [9][10][11][12][13][14][15] have been implemented to investigate the corrosion behaviors and mechanisms of boiler tubes. These studies are categorized into fireside corrosion and water/steamside corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Therein, the fireside corrosion attracts much more attention. For example, Xu et al [ 13 ] made an investigation on the corrosion properties of the waterwall (fireside) at high temperatures ospheres. Wang et al [ 9 ] studied the dew point corrosion behavior of the waterwall.…”
Section: Introductionmentioning
confidence: 99%
“…Pipe broken accidents in boilers have triggered off many severe economic and safety problems caused by corrosion. Some studies [4][5][6][7][8][9][10] have been conducted to figure out the corrosion behaviors of boiler tubes. These researches could be classified into fireside corrosion and working medium side corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Under normal operation of the incinerator, the corrosion of steel structures by hydrogen fluoride in the flue gas is negligible and the main source of corrosion is the sulphur containing gas. [13][14][15][16] Some researchers have also tested the corrosion effect of dry hydrogen fluoride gas on a variety of metals such as copper, nickel, white copper, and steel in a laboratory simulation of flue gas corrosion and found that only pure nickel, nickel-based alloys, and copper had good corrosion resistance, while mild steel had a corrosion rate of up to 1.56 cm/a. [17][18][19] The pitting effect of hydrides, particularly halogenated hydrides, on dense alloy materials has been a major focus of attention in research into the high temperature corrosion characteristics of dense alloy materials.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies on the corrosive effect of hydrogen fluoride, some researchers have stated that the contribution of fluorine to corrosion is extremely weak. Under normal operation of the incinerator, the corrosion of steel structures by hydrogen fluoride in the flue gas is negligible and the main source of corrosion is the sulphur containing gas 13–16 . Some researchers have also tested the corrosion effect of dry hydrogen fluoride gas on a variety of metals such as copper, nickel, white copper, and steel in a laboratory simulation of flue gas corrosion and found that only pure nickel, nickel‐based alloys, and copper had good corrosion resistance, while mild steel had a corrosion rate of up to 1.56 cm/a 17–19 …”
Section: Introductionmentioning
confidence: 99%